Using Routinely Collected Electronic Healthcare Record Data to Investigate Fibrotic Multimorbidity in England [Response to Letter] - Massen GM; Quint JK (Clinical Epidemiology, 2024)
Georgie M Massen, Jennifer K Quint School of Public Health, Imperial College London, London, UKCorrespondence: Georgie M Massen, School of Public Health, Imperial College London, 86 Wood Lane, London, SW7 2AZ, UK, Email g.massen21@imperial.ac.uk